A Compact Shorted Printed Monopole Antenna for TV White Space Trials - JOHN, MATTHIAS (My University, 2013)
This paper presents a compact shorted printed monopole antenna for machine-to-machine, remote sensing and rural wireless applications in the TV whitespace band from 470 MHz to 862 MHz. The antennas performance in this operating band is demonstrated.
European Conference on Antennas and Propagation - EuCAP
PUBLISHED
Gothenburg, Sweden
Keywords: Printed monopole; TV white space; Telecommunications